HUBUNGAN KELENTURAN OTOT PUNGGUNG DAN KEKUATAN OTOT TUNGKAI DENGAN HASIL SHOOTING SEPAK BOLA PADA ATLET PPLP RIAU - Darwis, Robi; Zainur, Zainur; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine the relationship between the flexibility of the waist muscles, leg muscles with the results of shooting PPLP Riau. Based on the type of data needed in this study are primary data that is data directly collected by researchers from the source through measurement tests, namely data about the flexibility and strength of leg muscles with accurate shooting (kick) to the goal. The results obtained from the flexibility of the waist muscles have a relationship with the results shooting in PPLP Riau soccer game is the acquisition of r count (0.443)> from the rtable acquisition (0.423) at Î± = 0.05. From the results obtained leg muscle strength has a relationship with the results of shooting in Riau PPLP soccer game that is the acquisition of rcount (0.592)> from the acquisition of rtable (0.423) at Î± = 0.05. There is a joint relationship between leg muscle strength and flexibility of the waist muscles to the shooting results in the PPLP Riau soccer game, namely the acquisition of Rhitung (0.635)> from the acquisition of Rtable (0.423) at Î± = 0.05.Key Words: Back Muscle Flexibility, Leg Muscle Strength, Shooting Results